Football innovation in Denmark - Design of a collaboration and activity model - Elbæk, L.; Vestergaard Andersen, R.; Engelhardt Hansen, R.; Couchouron, C. (2022)
As a collaboration between the Danish FA (Dansk Boldspil-Union), Danish League (Divisionsforeningen), University of Southern Denmark (SDU), and Odense Municipality the aim is to establish a football centre in Odense. Bringing together actors like the above-mentioned academia, industry, government, and civil society is important in order to strengthen regional innovation (Roman et al. 2020), and a collaboration model can be a way to communicate, interact, and attract relevant stakeholders. The aim of this project is to propose a collaboration model for the innovation centre that embraces the Nordic social innovation values and potentially improves the effectiveness of the collaboration between multiple stakeholders. Using the quadruple helix collaboration model of innovation as a theoretical starting point, the aim was to create a collaboration model recognising the Nordic value of social innovation and create an open system with the civil and business society as active stakeholders. Through a co-creational design research approach, workshops served the purpose of engaging the stakeholders` groups of Football Startup in Denmark, Football related NGOs, DBU, Divisionsforeningen, Football researchers at SDU, foundation staff and representatives from Odense Municipality informing, legitimising and validating the collaboration model. The final collaboration and activity model as illustrated to the left is a quadruple helix model representing the four main stakeholders: Academia as Research and Development (blue), the industry as Football and Sports industry (red), the Civil Society as Football Organisation (green) and the Policymakers as the public sector and private funds (yellow). The six design stages and process activities are shown on top of the stakeholders, illustrating the iterative design process to Engage, to identify Needs, to Match make stakeholders, to Develop and test artefacts of products and services, to Implement invented and developed artefacts and to evaluate Impact as illustrated in the figure below. These elements of innovation are comparable to a service, technology, and product design approach for stakeholders relevant to the innovation centre.